1992
DOI: 10.1073/pnas.89.9.3746
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and posttranscriptional regulation of 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase during liver regeneration.

Abstract: The control of 6-phosphofructo-2-kinase/ fructose-2,6-bisphosphatase (PFK-2/FBPase-2; EC 2.7.1.105/3.1.3.46) gene expression during liver regeneration was studied. The level of PFK-2/FBPase-2 mRNA decreased to about 5% of the control value 6 hr after partial hepatectomy. Thereafter the mRNA increased to a maximum at 48 hr and returned to normal levels by 96 hr. In sham-operated animals, only a small increase was observed during the first 4 hr. The mRNA was recognized by a 299-base-pair liver-specific cDNA prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 46 publications
4
16
0
Order By: Relevance
“…Transcription of the c-fos gene was only induced by 2.0-fold at 30 min (Fig. 2B, compare first two lanes) which is in agreement with the fact that regulation of expression of the c-fos gene in the regenerating liver is post-transcriptional (43). A darker exposure of the autoradiogram presented in Fig.…”
Section: Cat-1 Is a Delayed Early Response Gene In The Regeneratingsupporting
confidence: 71%
See 3 more Smart Citations
“…Transcription of the c-fos gene was only induced by 2.0-fold at 30 min (Fig. 2B, compare first two lanes) which is in agreement with the fact that regulation of expression of the c-fos gene in the regenerating liver is post-transcriptional (43). A darker exposure of the autoradiogram presented in Fig.…”
Section: Cat-1 Is a Delayed Early Response Gene In The Regeneratingsupporting
confidence: 71%
“…Expression of the genes involved in gluconeogenesis, PEPCK, and TAT also increases following partial hepatectomy (Fig. 1A) in order for the liver to maintain glucose homeostasis and compensate for the loss of mass (41)(42)(43). The level of the PEPCK mRNA, as expected, increased in 30 min and remained at the induced level until 6 h following hepatectomy (41)(42)(43).…”
Section: Cat-1 Is a Delayed Early Response Gene In The Regeneratingmentioning
confidence: 69%
See 2 more Smart Citations
“…Studies have shown that there is an acute fall in insulin and an increase in glucagon levels immediately after hepatectomy both of which begin to renormalize within a few hours, thereby preventing the hypoglycemia which might accompany the loss of liver mass (4,5). Previously, we and others (6)(7)(8)(9) showed that phosphoenol pyruvate kinase (PEPCK)' and other genes involved in glucose homeostasis are rapidly up-or downregulated in the regenerating liver, thus allowing the remnant liver to maintain glucose balance.…”
Section: Introductionmentioning
confidence: 99%